1987
DOI: 10.1515/zna-1987-0403
|View full text |Cite
|
Sign up to set email alerts
|

Borinine (Borabenzene): Its Structure and Vibrational Spectrum. A Quantumchemical Study

Abstract: Recently we reported the results of some semiempirical and ab initio studies in which we compared the electronic structure of the hitherto unknown borinine with those of benzene and pyridine. The results of our calculations led us to the conclusion that the elusive nature of borabenzene is caused by its high reactivity, which might at least in part be due to the pronounced σ acceptor properties of a low-lying σ* molecular orbital. We now present the results of further ab initio and semiempirical (MNDO) inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…[3] Cioslowski and Hay [4] studied borabenzene and its adducts with the donor molecules N 2 and CO. For the energies (enthalpies) of reaction for C 5 H 5 B with the donor molecules they obtained values of À19.2 and À42.9 kcal mol À1 (À16.4 and À39.4 kcal mol À1 ). According to their calculations, bonding between the donor molecules (N 2 , CO) on the one and borabenzene on the other hand primarily involves donation of a s lone pair of the ligand into a vacant low-lying s* orbital mainly located at boron and, in addition, a probably weak back donation into the p* orbitals of N 2 and CO. [4] As we did in our preceding communication, [2] Cioslowski and Hay attributed the high reactivity of borabenzene to the presence of an energetically low orbital of s symmetry. Moreover, the authors pointed out that the relief of strain within the borabenzene unit upon addition of the ligand might further contribute to the exothermicity of the reaction of the title compound with the donor molecules.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…[3] Cioslowski and Hay [4] studied borabenzene and its adducts with the donor molecules N 2 and CO. For the energies (enthalpies) of reaction for C 5 H 5 B with the donor molecules they obtained values of À19.2 and À42.9 kcal mol À1 (À16.4 and À39.4 kcal mol À1 ). According to their calculations, bonding between the donor molecules (N 2 , CO) on the one and borabenzene on the other hand primarily involves donation of a s lone pair of the ligand into a vacant low-lying s* orbital mainly located at boron and, in addition, a probably weak back donation into the p* orbitals of N 2 and CO. [4] As we did in our preceding communication, [2] Cioslowski and Hay attributed the high reactivity of borabenzene to the presence of an energetically low orbital of s symmetry. Moreover, the authors pointed out that the relief of strain within the borabenzene unit upon addition of the ligand might further contribute to the exothermicity of the reaction of the title compound with the donor molecules.…”
Section: Introductionmentioning
confidence: 69%
“…[1,2] In those calculations, we found that borabenzene in its ground state is planar, and like benzene, pyridine, and other aromatics, has three doubly occupied orbitals of p symmetry. However, its lowest unoccupied molecular orbital was found to be of s symmetry and to be mainly located at the boron atom.…”
Section: Introductionmentioning
confidence: 89%
“…Borabenzene (C 5 H 5 B) has been the subject of some experimental [1][2][3] and an even higher number of theoretical [4][5][6][7][8][9][10][11][12] studies; however, attempts to generate the free compound have met with failure so far. At least in two experimental studies, borabenzenze apparently occurred as a transient that was trapped either by dinitrogen [1] or pyridine.…”
Section: Introductionmentioning
confidence: 99%
“…The first borole-containing mixed-metal cluster, [Re 2 Pd 2 (g 5 This unusual Re 2 Pd 2 cluster displayed a unique bonding mode of the borole ligand which not only binds to rhenium in the usual g 5 manner but also to the adjacent palladium via a 2e-3c B-C ipso -Pd system. This led us to extend our studies on borole-containing carbonylmetallates to the 2-boratanaphthalene systems 4a,b.…”
Section: Introductionmentioning
confidence: 99%
“…Borabenzene 8 does not exist due to a low-lying in plane r*type LUMO which is essentially localized at the boron atom. 4,5 Therefore stabilization by a Lewis base is necessary and is achieved in the amino-substituted boratabenzene 9. 6,7 The first boratabenzene complex was obtained in 1970 from a cobaltocene 8 while Li(TMPA)(C 5 H 5 BNMe 2 ) (TMPA = Me 2 N(CH 2 ) 3 NMe 2 ) was, in 1993, the first boratabenzene salt structurally characterized.…”
Section: Introductionmentioning
confidence: 99%